Implementation of Occupational Safety and Health (K3) in Community Workers of Pulau Pinang, Malaysia - Isradi, Muhammad; Amin, Mawardi; Hidayat, Acep; Susetyo, Budi; Vidayanti, Desiana; Indriany, Syilvia; Biantoro, Agung Wahyudi; Jawu, Patricia Kanicia (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
Based on data from Bank Indonesia, there are 1.67 million Indonesian migrant workers in Malaysia, both in the formal and non-formal sectors. One of the destinations for Indonesian migrants is Pulau Pinang, Malaysia. PERMAI stands for Pertubuhan Masyarakat Indonesia di Pulau Pinang Malaysia, which is a non-governmental, non-political NGO engaged in social education and culture. Efforts to apply occupational safety and health (K3) to workers are very important for workers when carrying out work activities. Especially for employees who work in a work environment that has high safety and health risks, work safety in the company is not only caused by the system that has been implemented by the company but also by the awareness of everyone to avoid work accidents. The purpose of this activity is to provide an introduction to occupational health and safety (K3) to business owners and workers who are in Pulau Pinang, Malaysia, and to equip business owners and workers to apply K3 in their work activities to prevent injuries, occupational diseases, or accidents. The method used in this activity is to provide health promotion counseling on occupational health and safety. This counseling uses media in the form of leaflets and provides pre- and post-tests in the form of questions and questionnaires to workers to determine their knowledge and understanding. The evaluation results show that the level of compliance with wearing personal protective equipment ("APD") is still low, with a percentage of 37%. Based on the IPA Cartesians diagram, variables X5, X6, and X8 are variables that have importance and good performance.